Technical efficiency and productivity of public district hospitals in KwaZulu-Natal province, South Africa - Tesleem K. Babalola; Indres Moodley (SAGE Publishing, 2020)
Background: District hospitals (DHs) constitute a significant proportion of public hospitals and consume a more substantial percentage of the government's total hospital budget. With the level of resources disbursed to DHs, it is essential to ensure efficient allocation and utilization. Hence, this study set out to assess the technical efficiency and productivity of public DHs in KwaZulu-Natal province, South Africa. Methods: Data envelopment analysis (DEA) and Malmquist total factor productivity (MTFP) were used to assess technical efficiency, identify adjustments required to make inefficient facilities more efficient, and determine overall productivity growth. Input data such as medical personnel and output information such as outpatient visits were retrieved from the databases of the district health information system (DHIS), and personnel salary systems (PERSAL) for three consecutive financial years (2014/15, 2015/16 and 2016/17). A total of 38 district hospitals were included in the study. Results: The proportion of technically efficient facilities according to constant return to scale (CRS) were 12 (31.6%), 16 (42.1%) and 14 (36.8%) in 2014/15, 2015/16 and 2016/17, respectively, while according to the variable return to scale (VRS) technically efficient facilities were 22 (57.9%), 19 (50.0) and 21 (55.2%), respectively, for the three consecutive years. On average, the total productivity of DHs increased by 4.8 percent over the three years, which is attributed majorly to technical growth of 6.9 percent. Conclusion: This study showed that a significant proportion of the district hospitals were technically inefficiency. Also, steps that could enable more efficient use of healthcare resources to yield optimal health service delivery were recommended.